Methods for assessment and testing students? learning outcomes in cooperative teaching = Metody oceniania i testowania efektów kształcenia studentów w nauczaniu we współpracy - Nguyen, Thi Thanh (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents some methods for assessing and testing student learning outcomes in cooperative teaching in order to help lecturers to assess objectively as well as to clearly present the results achieved by various groups and individuals. Understanding the basics of assessment can have a positive impact on every student. It is essential to adjust the methods of assessment to teaching and create incentives that will increase students' interest in learning
Keywords: metody oceniania i testowania; nauczanie kooperatywne; metody realizacji; zachowania kooperatywne; umiejętności kooperatywnego uczenia się; assessment and testing methods; cooperative teaching; method of implementation; cooperative behaviors; cooperative learning skills